Evaluation of food safety knowledge, attitude, practices and hand contamination of food handler in Islamic school - Ismail, Muhammad Hazim (2019)
The importance of food safety knowledge, attitude and practice (KAP) issues for food handlers in schools has been addressed on account of food poisoning cases. Staphylococcus aureus had been reported as third most pathogens that caused food borne disease in the world. This study is aims evaluate food safety knowledge, attitudes practices and hand contamination among the food handlers at Islamic school canteen in Tangkak,Johor. The level of food safety knowledge, attitudes and practices of food handlers will be evaluated using a structured questionnaire. The count of staphylococcus aureus excess using rapid test kit (Petri film). The result showed food handlers had good level of knowledge (84.63%), attitude (85.27%) and practice (85.39%). There was a negative good correlation between food safety knowledge ,attitude practices level and counts of staphylococcus aureus on food handler hand .The finding of Pearson Correlation between Knowledge and Staphylococcus aureus counts is (r = -694, n=33, p<0.001), Attitude level and staphylococcus aureus counts is (r = -623, n=33, p<0.001) and Practice level and staphylococcus aureus counts is (r = -549, n=33, p<0.001)